Six Sigma pada UMKM Rina Payakumbuh Untuk Minimasi Defect Produk Sanjai - Marlina, Winny Alna; Khairi, Khairi; Poni, Poni (Jurnal Manajemen, 2020)
Based on Survey data in 2018, Payakumbuh has a cracker industry of 44%, a wet cake industry 37%, 11% of the food industry which is not yet included in any group, and 8% of the bread and similar industries. One of the SMEs that produce Sanjai in Payakumbuh is Sanjai Rina. Sanjai Rina's business has been established since 1990. The production system at Sanjai Rina is still simple in its processing, so there are defective products every month. The number of defects in December 2018 will be 50 kg, with a production of 3300 kg. For this reason, Six Sigma at Rina Payakumbuh MSMEs for Minimizing Defect Sanjai Products. The use of Six Sigma to prevent and reduce product defects, save costs, and customer satisfaction. Results Sigma scores of Sanjai defective products at Rina's UMKM were 4% and exceeded Sigma's standard by 3%. In minimizing defects in Sanjai products by using the Six Sigma methodology, which includes DMAIC. Sanjai Rina's product damage classification consists of 32% because the packaging is caused by plastics exposed to the heat of the frying pan, 29.8% due to expired products, and 38.2% technical problems, namely a large number of requests by the retailer due to running out of stock. Technical errors cause the most significant product defect, so UKM Rina will provide training to employees and provide training in producing sanjai to minimize the number of defective products to increase company profits.